2022
DOI: 10.3389/fendo.2021.803024
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Disorders of Thyroid Hormone Metabolism Defect Caused by the Dysregulation of Selenoprotein Expression

Abstract: Consistent activation and functioning of thyroid hormones are essential to the human body as a whole, especially in controlling the metabolic rate of all organs and systems. Impaired sensitivity to thyroid hormones describes any process that interferes with the effectiveness of thyroid hormones. The genetic origin of inherited thyroid hormone defects and the investigation of genetic defects upon the processing of thyroid hormones are of utmost importance. Impaired sensitivity to thyroid hormone can be categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…Disorders of handling iodide along its path to TH, which impair the functions of TSHR, NIS, TG, TPO, DUOX/DUOXA2 and IYD, are known [ 19 ]. Similarly, (inherited) genetic disorders and variants of the selenoproteins required for TH biosynthesis and metabolism as well as the protection of the H 2 O 2 -exposed thyroid follicular structure have been identified [ 20 ]. Such alterations modify the sensitivity of the hypothalamus–pituitary–thyroid–periphery (HPTP) axis to its negative feedback regulation by TH and its adaptive response to nutritional, environmental, pharmacological and disease-related challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of handling iodide along its path to TH, which impair the functions of TSHR, NIS, TG, TPO, DUOX/DUOXA2 and IYD, are known [ 19 ]. Similarly, (inherited) genetic disorders and variants of the selenoproteins required for TH biosynthesis and metabolism as well as the protection of the H 2 O 2 -exposed thyroid follicular structure have been identified [ 20 ]. Such alterations modify the sensitivity of the hypothalamus–pituitary–thyroid–periphery (HPTP) axis to its negative feedback regulation by TH and its adaptive response to nutritional, environmental, pharmacological and disease-related challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, present study found signi cant association between rs11548 polymorphism and increased PCOS risk. Selenocysteine as structural amino acid for thyroid deiodinases (DIO1, DIO2) were dependent upon blood selenium concentration for their biological activities such as homeostasis and thyroid hormone regulation [45]. In vivo study evaluated the dietary selenium effect among selenoprotein genes which shows decreased mRNA expression of GPX2, GPX3, and DIO2 genes and no effect on DIO1 and TXNRD1 gene expression [46].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with severe COVID-19 frequently experience a strong systemic inflammatory response, which may have an effect on how thyroid hormones are transformed and released ( 25 ). For instance, inflammation may cause cystosulfate deiodinase (DIO2) to function less efficiently, which may influence the conversion of T4 to T3 ( 26 ). Also, the virus might directly or indirectly invade thyroid tissues, causing inflammation and cellular damage ( 27 ).…”
Section: Discussionmentioning
confidence: 99%